The Association Between Exercise During Pregnancy and the Risk of Preterm Birth - Zhang J; Xiao Y; Bai S; Lin S; Du S; Wang Z (International Journal of Women's Health, 2024)
Jin Zhang,1,* Yang Xiao,2,* Shuoxin Bai,3 Shaoqian Lin,2 Shuang Du,1 Zhiping Wang4 1Department of Occupational and Environmental Health, School of Public Health, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People’s Republic of China; 2Center for Disease Control and Prevention, Jinan, Shandong, 250021, People’s Republic of China; 3Department of Epidemiology, School of Public Health, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People’s Republic of China; 4School of Public Health, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhiping Wang, School of Public Health, Cheeloo College of Medicine, Shandong University, 44 Wenhuaxi Road, Jinan, Shandong, 250012, People’s Republic of China, Email zhipingw@sdu.edu.cnPurpose: We aimed to examine the association between exercise during pregnancy and preterm birth (PTB).Methods: This study was a baseline survey of the Jinan birth cohort. The study subjects were the mothers one month after giving birth, which were investigated by questionnaires retrospectively containing physical exercise (frequency, time, and primary exercise patterns) during pregnancy and each trimester. Individual time spent on exercise and energy expenditure were assessed based on the questionnaires. PTB was clinically defined as a newborn born on or before the last day of the 37th week. Adjusted odds ratios (OR) were estimated using logistic regression to assess the relationship between exercise during pregnancy and the risk of PTB. Variable selection for the multivariate models was guided by the directed acyclic graph. The median effect was analyzed by the sequential test.Results: The prevalence of PTB in this study was 4.38% (285/6501). The adjusted OR (95% CI) for the risk of PTB related to exercise during pregnancy was 0.74 (0.58– 0.95). During the 1st and 2nd trimesters, the ORs (95% CI) for 2.5 to 7 hours of exercise per week were 0.77 (0.59– 0.99) and 0.74 (0.57– 0.96). During the 3rd trimester, the ORs (95% CI) for 2.5 to 7 hours and more than 7 hours of exercise per week were 0.74 (0.56– 0.96) and 0.65 (0.44– 0.94). After stratifying the subjects, the association was only found among subjects without pregnancy complications. Pregnancy complications partially mediated (52.40%) the relationship between exercise during pregnancy and PTB.Conclusion: Exercise during pregnancy can reduce the risk of PTB for women without pregnancy complications. 2.5 to 7 hours of exercise (like walking) per week may be appropriate in three trimesters of pregnancy, and the time could be extended in the 3rd trimester.Keywords: pregnant women, exercise, trimester, mediation analysis